Lessons Learned Using ArchC in Computer Architecture Laboratory - Azevedo, Rodolfo; Wanner, Lucas (International Journal of Computer Architecture Education, 2016)
This paper presents a set of laboratory experiments based on the ArchC Architecture Description Language designed to fulfill the practical knowledge on Computer Architecture. These activities were designed over the last years and have been used in our discipline of Laboratory of Computer Architecture, where seventh semester students apply the knowledge they acquired in the theory classes. We present the experiments, covering 10 distinct topics in Computer Architecture, along with specific sections of the text-book to which they refer. We also show some of the experiences we acquired during the last years both on learning outcomes and student feedback.